2019
DOI: 10.21873/anticanres.13590
|View full text |Cite
|
Sign up to set email alerts
|

Italian Cohort of the Nivolumab EAP in Squamous NSCLC: Efficacy and Safety in Patients With CNS Metastases

Abstract: Background/Aim: Brain metastases are an additional challenge in patients with non-small-cell lung cancer (NSCLC) because most chemotherapy agents cannot cross the bloodbrain barrier. Nivolumab has demonstrated efficacy in patients with advanced squamous NSCLC, but because patients with central nervous system (CNS) metastases are typically excluded from registration trials, 'field-practice' data are needed. Patients and Methods: Patients in the Italian cohort of the Expanded Access Program (EAP) who had CNS met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…The vast majority of the real-world data about immunotherapy in lung cancer describes the activity, in terms of objective response rate (ORR), efficacy (in terms of overall survival, OS, and progression free survival, PFS) and the safety profile of the most common ICIs used in clinical practice (Table 1). Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23].…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 76%
“…The vast majority of the real-world data about immunotherapy in lung cancer describes the activity, in terms of objective response rate (ORR), efficacy (in terms of overall survival, OS, and progression free survival, PFS) and the safety profile of the most common ICIs used in clinical practice (Table 1). Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23].…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 76%
“…Several expanded access programs and observational studies examining patients with NSCLC treated with singleagent PD-1 or PD-L1 inhibitors found that clinical outcomes (including efficacy and safety) were similar in patients with versus without brain metastases, highlighting that both PD-1 and PD-L1 inhibitors can be effective in patients with CNS disease. [22][23][24][25] A limitation of this study is that we only allowed patients with brain metastases between 5 and 20 mm; this was chosen to avoid neurologic compromise in the event of tumor growth. Additionally, we did not evaluate patients with neurologic symptoms or those that required corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab therapy is routinely used in patients who have undergone primary resection or irradiation for brain metastases and whose clinical condition improved after receiving local treatment. Retrospective analyses of real-world data showed that nivolumab has intracranial activity [ 19 , 20 , 21 ]. Twenty-six percent of patients with non-squamous NSCLC in the Italian EAP had asymptomatic or controlled brain metastases [ 19 ].…”
Section: Nivolumab In Daily Practicementioning
confidence: 99%
“…In the cohort with squamous NSCLC, 10% of 372 patients had asymptomatic brain metastases. The median OS was 5.8 months (95% CI 1.9–9.8) [ 21 ]. A direct comparison of the efficacy of nivolumab in patients with and without brain metastases showed significant differences in OS [ 14 ].…”
Section: Nivolumab In Daily Practicementioning
confidence: 99%